Alternative use of water treatment plant sludge in paving: a review (Research, Society and Development, 2020)
Rapid urban and population growth has increased demand for drinking water. Consequently, large amounts of sludge are generated in the decanters of the Water Treatment Plants (ETA) as a result of the treatment process. This residue, when not disposed of correctly, can become a contaminant to the environment. The present work aims to present through a literature review study alternative forms for the application of ETA sludge in road paving with emphasis on the aggregate used for stabilization and leaching process, in order to evaluate an environmentally correct destination. Through the literature studied it is possible to conclude that sludge can be applied in the paving layers (base, sub-base and subbed), in bituminous concrete and concrete for the recomposition of sidewalks. With regard to stabilization, the use of cement, hydrated lime and soil is perceived. Regarding the leaching process, there is a greater presence of Mn, Fe, Al, Cd, Pb and Ni in several studies that contemplate this test.